2017
DOI: 10.1186/s12931-017-0587-9
|View full text |Cite
|
Sign up to set email alerts
|

Which bronchodilator reversibility criteria can predict severe acute exacerbation in chronic obstructive pulmonary disease patients?

Abstract: BackgroundIt is unclear whether various bronchodilator reversibility (BDR) criteria affect the prognosis of chronic obstructive pulmonary disease (COPD). The aim of this study is to evaluate the impact of positive BDR defined according to various BDR criteria on the risk of severe acute exacerbation (AE) in COPD patients.MethodsPatients from four prospective COPD cohorts in South Korea who underwent follow-up for at least 1 year were enrolled in this study. The assessed BDR criteria included the Global Initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the COPD group, 58.7% of patients had positive response to salbutamol, which is considered to be associated with better prognosis in terms of reduced risk of severe acute exacerbations [ 34 ]. The TRPA1 rs959976 polymorphism significantly influenced the response both qualitatively and quantitatively.…”
Section: Resultsmentioning
confidence: 99%
“…In the COPD group, 58.7% of patients had positive response to salbutamol, which is considered to be associated with better prognosis in terms of reduced risk of severe acute exacerbations [ 34 ]. The TRPA1 rs959976 polymorphism significantly influenced the response both qualitatively and quantitatively.…”
Section: Resultsmentioning
confidence: 99%
“…However, the clinical significance of spirometric BDR in patients with COPD remains controversial. Numerous studies have reported no association between spirometric BDR and exacerbations, mortality, or hospitalization rates in patients with COPD after adjusting for baseline function [ 6 , 7 , 9 ], however, a few studies have presented contrary conclusions [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-bronchodilator spirometry is required for the diagnosis of chronic obstructive pulmonary disease (COPD), but the role of bronchodilator response (BDR) is unclear in COPD (1). Positive bronchodilator reversibility is no longer recommended as a treatment option for COPD, and there is no standard definition yet (2,3). In addition, positive bronchodilator reversibility does not predict the clinical outcomes of long-term use of bronchodilators and inhaled corticosteroid (ICS) (4).…”
Section: Introductionmentioning
confidence: 99%